Two methods of fertilization in the cultivation of hybrid pineapple (Ananas sativus) MD2 (Revista Sistemas de Producción Agroecológicos, 2018)
Pineapple cultivation has a high production in Latin America and has increased its production in recent years in countries such as Uruguay, Brazil, Ecuador, Costa Rica and Colombia, from the hand of processes of social development, which has benefited many farmers. This experiment was carried out in San Martin, Meta, Colombia, where the pineapple variety MD2 was planted at distances of 30 cm between plants by 40 cm between lines in bed and one meter between beds; evaluation of two application methodologies was carried out: both cases with exact dose; and were compared with a control (T3) where no fertilizer was applied. In this project a randomized complete block design was established, with three treatments and five repetitions, each repetition was constituted by 120 plants per bed (600 plants per treatment), which corresponded to an experimental unit, evaluating every 15 days (15, 30. 45 and 60 days) five plants/bed/repetition, under an analysis of variance with Duncan's comparison test. At 15 and 30 days of evaluation T1 and T2 presented the highest plant heights (P
Keywords: fertilizer; fruit; root system; leaves